The light of the world : a memoir - Alexander, Elizabeth, 1962- (Grand Central Publishing, 2015)
" In THE LIGHT OF THE WORLD, Elizabeth Alexander--poet, mother, and wife--finds herself at an existential crossroads after the sudden death of her husband, who was just 49. Reflecting with gratitude on the exquisite beauty of her married life that was, grappling with the subsequent void, and feeling a re-energized devotion to her two teenage sons, Alexander channels her poetic sensibilities into a rich, lucid prose that describes a very personal and yet universal quest for meaning, understanding, and acceptance. She examines the journey we take in life through the lens of her own emotional and intellectual evolution, taking stock of herself at the midcentury mark. Because so much of her poetry is personal or autobiographical in nature, her transition to memoir is seamless, guided by her passionate belief in the power of language, her determination to share her voyage of self-discovery with her boys, and her embrace of the principle that the unexamined life is not worth living. This beautifully written book is for anyone who has loved and lost. It's about being strong when you want to collapse, about being grateful when someone has been stolen from you--it's discovering the truth in your life's journey: the good, the bad, and the ugly. It's Elizabeth Alexander's story but it is all of our stories because it is about discovering what matters"--